Strategi Pencegahan HIV melalui Bimbingan Layanan Konseling di RSUD Provinsi NTB - Syachar Suryawan (Dinasti Research, 2026)
HIV is a virus that attacks and damages the body's immune system, while the collection of symptoms it causes is known as AIDS. HIV/AIDS is a problem that threatens people worldwide and must be addressed, especially among the younger generation who remain vulnerable to risky behavior. This study aims to determine the HIV prevention strategy through counseling guidance services at RSUD Provinsi NTB. This research used a qualitative approach with a case study design. Data were collected through interviews, observation, and documentation. Data analysis applied data collection, data condensation, data display, and data verification, while data validity was checked through credibility, dependability, confirmability, and transferability. The results show that: (1) the HIV prevention strategy at RSUD Provinsi NTB is carried out through communication, condom use, and Antiretroviral Therapy (ART); (2) the counseling guidance approach is conducted through Voluntary Counseling and Testing (VCT) and Provider Initiated Testing and Counseling (PITC); and (3) the obstacles faced by health workers are patients' lack of awareness and willingness to take medication as well as mental health problems.